Eksplorasi Keanekaragaman Anggrek Epifit di Kawasan Konservasi Wilayah II Senduro, Blok Ireng-Ireng, Taman Nasional Bromo Tengger Semeru, Jawa Timur - Pandji Dimas Febriandito; Lita Soetopo (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2019)
Indonesia forest have high diversity of plants germaplasm, such as: moss, industrial food plant and ornamental plant. One of ornamental plant in the forest is orchid. Epiphytic orchid is a commensalism symbiote plant with the host tree. Many forest in Java converted to agricultural, industrial sectore so the population of epiphytic orchid start to be endangered (Puspitaningtyas, D.M., 2007). This is descriptive research with survey method. The purposes of the research were to know the diversity of epiphytic orchid and as consideration material of conservancy policy making by government. This research was conducted at Conservation Section Area II, Senduro, Ireng-Ireng Block, Bromo Tengger Semeru National Park, Lumajang, East Java in January until February 2018. This research used 30 obervation plots with measuring size 20 x 20 m and 100 m interval per plot. Vegetation analized were: density, relative density (RD), frequency, relative frequency (RF), important value index (IVI)and Shannon-Wiener diversity index. Orchid of Java book used to identified orchid. This research found 19 host trees of epiphytic orchid, has been sucsessfully identified 15 genera and 39 species with total population 1245.The dominate species was Eria javanica with IVI value 27.46%, relative density (RD) 8.19%. Orchids with the lowest IVI value (0.68%) were Appendicula ramosa, Malleola ligulata, Taeniophyllum sp. and Trixspermum purpurasccens, relative density (RD) were 0.08% and relative frequency (RF) were 0.58%. According to Shannon-Wiener diversity index value (2.90), the epiphytic orchid diversity in this area can be categorized in “medium state”.